Grafting with an invasive Xanthium strumarium improves tolerance and phytoremediation of native congener X. sibiricum to cadmium/copper/nickel tailings. (December 2022) - Xue, Chenyang; Sun, Lizong; Qu, Bo; Gao, Yingmei; Liu, Zhi; Guo, Cheng; Liu, Wanbin; Chang, Wenyue; Tai, Peidong
Abstract: Invasive plants could play an important role in the restoration of tailings, but their invasiveness limits their practical application. In this study, the phytoremediation potentials and invasive risks of an exotic invasive plant ( Xanthium strumarium, LT), a native plant ( X. sibiricum, CR), and combinations of inoculations (EG, with CR as the scion and LT as the rootstock; SG, with CR as both the scion and rootstock) were evaluated on Cd/Cu/Ni tailings. LT rootstock has a stronger nutrient and metal transport capacity, compared with CR. EG not only had higher biomass and Cd/Cu/Ni accumulation, but also abundant rhizosphere microbial communities. Hydroponic and common garden experiments showed that the growth and metal enrichment characteristics of EG are not inherited by plant offspring, which reduces the risk of the biological diffusion in the process of using exotic species. Transcriptome analysis shows that a large number of differentially-expressed genes in EG leaves and roots are involved in phenylpropanoid biosynthesis, secondary metabolite generation, and signal transduction. The genes induced in EG leaves, including cyclic nucleotide-gated ion channel, calcium-binding protein, and WRKY transcription factor, were found to be differentially expressed compared to CR. The genes induced in EG roots, included phenylalanine ammonia-lyase, cinnamoyl-CoA reductase, caffeoyl-CoA O-methyltransferase, and beta-glucosidase. We speculate that lignin and glucosinolates play an important role in the metal accumulation and transportation of EG. The results demonstrate that grafting with LT not only improved CR tolerance and accumulation of Cd, Cu, and Ni, but also created a beneficial microbial environment for plants in tailings. More importantly, grafting with LT did not enhance the invasiveness of CR. Our results provide an example of the safe use of invasive plants in the restoration of Cd/Cu/Ni tailings. Graphical abstract: Image 1 Highlights: The grafting with Xanthium strumarium (LT) not only significantly enhances biomass and metal accumulation of X. sibiricum (CR), but rhizosphere microbial community abundance. Lignin and glucosinolates may play important roles in metal accumulation and transportation of EG (CR/LT). The grafting with LT did not enhance the invasiveness of CR. The reasonable utilization of exotic plants not only gives full play to the phytoremediation potential, but also can help turn waste material into valuable resources.